EDUCATIONAL POLICY OF ETHNIC-RACIAL RELATIONS: THE SPECIFICS AND DIRECTION OF BRAZILIAN LEGISLATION - Edilson Fernandes Souza; Maria Conceição Reis; Vilde Gomes Menezes (Editora da Universidade de Santa Cruz do Sul, 2013)
In order to understand the structure of educational policies in regards to etnic-racial relations throughout the history of Brazilian education and identify how these come to configure legislation, this article proposes to answer following question: which specific details and directions have educational policies been drawing in regards to etnic-racial issues through the Brazilian legislation? We seek, therefore, to outline the path of the characteristics of the Brazilian school educational system regarding this etnic-racial theme from the time of the colonial period to the present days, going through past Constitutions until the specific present national educational legislation on this topic: law nº 10.639/2003. Along the way, we point out the difficulties that the Afro-Brazilian population faced and faces when it comes to the interpretation of the laws and the implementation of educational policies that favor etnic-racial relations. Keywords: Educational policies; Etnic-racial Relations within Education; Brazilian Educational Legislation; Law nº 10.639/2003.